2016
DOI: 10.3389/fcell.2016.00088
|View full text |Cite
|
Sign up to set email alerts
|

The Under-Appreciated Promiscuity of the Epidermal Growth Factor Receptor Family

Abstract: Each member of the epidermal growth factor receptor (EGFR) family plays a key role in normal development, homeostasis, and a variety of pathophysiological conditions, most notably in cancer. According to the prevailing dogma, these four receptor tyrosine kinases (RTKs; EGFR, ERBB2, ERBB3, and ERBB4) function exclusively through the formation of homodimers and heterodimers within the EGFR family. These combinatorial receptor interactions are known to generate increased interactome diversity and therefore influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 102 publications
(173 reference statements)
5
47
0
Order By: Relevance
“…There is corroborating evidence that Eps8 expression facilitates neural cell motility; in rat neural cell lines and in SVZ explants Eps8 has been shown to function in NRG1-Erb4 stimulated migration (Fregnan et al 2011). Erb4 is a EGFR family receptor, and the members of this family signal through very similar transduction pathways likely to include Eps8 (Kennedy et al 2016). Moreover, the regulation of Eps8 in NPCs provides a likely mechanism underlying our previously reported decrease of Nestin expressing cells in neurosphere cultures from mice lacking Hnrnpab.…”
Section: Hnrnpab Regulates Cell Motility and Eps8 Gene Expression In supporting
confidence: 66%
“…There is corroborating evidence that Eps8 expression facilitates neural cell motility; in rat neural cell lines and in SVZ explants Eps8 has been shown to function in NRG1-Erb4 stimulated migration (Fregnan et al 2011). Erb4 is a EGFR family receptor, and the members of this family signal through very similar transduction pathways likely to include Eps8 (Kennedy et al 2016). Moreover, the regulation of Eps8 in NPCs provides a likely mechanism underlying our previously reported decrease of Nestin expressing cells in neurosphere cultures from mice lacking Hnrnpab.…”
Section: Hnrnpab Regulates Cell Motility and Eps8 Gene Expression In supporting
confidence: 66%
“…Accordingly, a number of therapeutic approaches have been devised to target RTK activity, either through neutralizing antibodies or small molecule kinase inhibitors. As a general therapeutic mechanism, targeting RTK activity will usually elicit a strong initial response, but relapse invariably occurs due to a number of avenues of therapeutic resistance (Kennedy et al, ).…”
Section: Potential Applications For Modelling Of Matrix Signallingmentioning
confidence: 99%
“…At the very least, we have shown that affinity values from the original publications were derived from data and methods causing serious inaccuracies. This data has had a wide-reaching effect in many areas of SH2 domain research: the data has been used to draw specific conclusions about SH2 domain biology such as identification of EGFR recruitment targets (33), to explain quantitative differences in RTK signaling (9), and as evidence to understand the promiscuity of EGFR tail binding (34). In addition, this work has been used to guide experimental design by filtering potential binding proteins by affinity (35), to reconcile confusing experimental results (36), and to guide new experimental hypothesis testing (37).…”
Section: Discussionmentioning
confidence: 99%